Changes in Prospective Biology Teachers’ Mental Model OF Virus through Drawing-Writing Test: An Application of Mental Model-Based Microbiology Course (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The main goal of the present research was to analyze the prospective biology teachers’ mental model about virus through the conduction of drawing-writing test on a modified model-based learning in a Microbiology course. The research method was quasi-experiment with pretest-posttest control group design. A total of eighty-one fifth-semester students separated into experiment and control group participated in the current study. The experiment class participated in a microbiology course-based mental model, in which the course program was developed by combining the constructivism learning stages and model-based learning framework featured with mental model, while the control class experienced course with conventional methods. A mental model test of drawing-writing of structure of viruses was employed as the main research instrument. The instrument also was featured with a rubric that is used to indicate the five levels of student’s mental model. The main analysis was done through descriptive interpretation based on the frequency of higher levels of mental model showed by students in the different classes. Based on the results, there was no difference between students in experiment and control class in the pretest, which showed that most of the students in both class were concentrated in not higher than level D3 and W3 (partially correct drawing/writing). However, after an intervention, the experiment class showed a dramatically increase in the frequency of students mental model that belong to level D5/W5 (completely correct and complete drawing/writing), while the control group was found stagnant concentrated in the level D3/W3. The results are discussed with the connection to the advantages of Microbiology course-based mental model in student’s conceptual change and the use of drawing-writing test in capturing changes in student’s mental model about scientific concepts.